2020
DOI: 10.4049/immunohorizons.2000086
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Undergraduate Immunology Education: Can a Comprehensive Four-Year Immunology Curriculum Answer Calls for Reform in Undergraduate Biology Education?

Abstract: The field of immunology is rapidly evolving and has significant relevance to understanding human health, particularly in light of the threat from infectious diseases and the ability to harness the immune system to treat cancer, autoimmune diseases, and allergies. Providing opportunities to explore the field of immunology is relevant to undergraduate students interested in pursuing careers in health professions and biomedical research. There are calls for greater emphasis on interdisciplinary science education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…explores the comparison of immunology as a discipline to neuroscience, which have many intellectual similarities to immunology but is significantly more highly represented in the number of undergraduate majors and discusses the potential reasons why this might occur. This article, as well as a recently published paper ( 2 ), details how undergraduate teaching and the curriculum might be changed to enhance Immunology a paradigm for interdisciplinary courses. Chatterjea discusses teaching immunology as a liberal art and emphasizes how immunology is not a single story.…”
Section: Diversity Of Approaches In Undergrad Teachingmentioning
confidence: 99%
“…explores the comparison of immunology as a discipline to neuroscience, which have many intellectual similarities to immunology but is significantly more highly represented in the number of undergraduate majors and discusses the potential reasons why this might occur. This article, as well as a recently published paper ( 2 ), details how undergraduate teaching and the curriculum might be changed to enhance Immunology a paradigm for interdisciplinary courses. Chatterjea discusses teaching immunology as a liberal art and emphasizes how immunology is not a single story.…”
Section: Diversity Of Approaches In Undergrad Teachingmentioning
confidence: 99%
“…The University of Alabama at Birmingham (UAB) offers a unique 4-year undergraduate immunology major. Students in this program take an introductory immunology course in their sophomore year, concomitantly with courses in the introductory biology and chemistry series (22). Thus, students in the introductory immunology course have varied scientific knowledge, based on the sequence of courses they have completed.…”
Section: Introductionmentioning
confidence: 99%
“…Few resources are available that use a methodical approach to capture the key topics for inclusion in the course. In recognition of the critical need for enhanced guidance on undergraduate immunology curricular development, several recent publications have begun the process of advocacy around a more-unified approach to undergraduate immunology education (3,4). Of note, a recent study that reported the results of surveyed immunology educators has helped identify current curricular practices by experienced instructors, which has highlighted curricular priorities for both course and curriculum design for the field (5).…”
Section: Introductionmentioning
confidence: 99%
“…Novel ideas and cutting-edge teaching strategies have been shared at the AAI Annual Meeting and in a special section of the AAI Newsletter that is dedicated to pedagogy. The rising interest in immunology education is also reflected in recently published articles, which have begun to highlight effective teaching pedagogies and topics to cover (4,9,10).…”
Section: Introductionmentioning
confidence: 99%